The place of historical and archaeological research in the system of forensic examinations - K. P. Sylenok (Bulletin of Kharkiv National University of Internal Affairs)
The theory of forensic science has long been supplemented by additional classifications, which differed in certain criteria and comprehensively reflected the essence of forensic science and expert research. The issue of forensic examinations classification in Ukraine according to the criteria existing in the doctrine and normative legal acts has been considered. The purpose of the study is the correct classification of historical and archaeological examination in the system of forensic science of Ukraine, to determine the main aspects and criteria for the classification of forensic science in Ukraine. To solve this goal, the scientific literature and regulatory support on the topic have been analyzed. It has been concluded that the historical and archaeological examination does not belong to the already existing types, as it has a unique subject, object and methods. It can be classified according to various criteria presented in the article.